2017
DOI: 10.7819/rbgn.v0i0.2302
|View full text |Cite
|
Sign up to set email alerts
|

Sex and gender identity differences in psychological job outcomes among salespeople

Abstract: Purpose -The purpose of this study was to determine whether there was any difference among sex and gender identity groups for salespeople in terms of psychological job outcomes, namely job stress, organizational commitment, intention to leave, and job satisfaction.Design/methodology/approach -Data was collected from salespeople using a survey. The questionnaire used was administered to a convenience sample of pharmaceutical salespeople from south-central region of Turkey, through a self-administered questionna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 44 publications
0
1
0
2
Order By: Relevance
“…Additionally, it has been demonstrated that gender matters and that female employees fare better than male ones in terms of success. Tanrikulu (2017) studied psychological outcomes of job, job stress, organizational commitment, reason for leaving, and job happiness to see if there were any differences based on gender identity. With the exception of work stress, they discovered that there were variations between sex groups in psychological work outcomes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Additionally, it has been demonstrated that gender matters and that female employees fare better than male ones in terms of success. Tanrikulu (2017) studied psychological outcomes of job, job stress, organizational commitment, reason for leaving, and job happiness to see if there were any differences based on gender identity. With the exception of work stress, they discovered that there were variations between sex groups in psychological work outcomes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Yağcı ve İlarsan (2010), Tüketicilerin gelir düzeyi yükseldikçe, cinsiyetler arasındaki ayrımlar azaldığını ortaya koymuştur (Yağcı ve İlarsan, 2010, s. 150). Tanrıkulu (2017), satış gücündeki iş sonuçlarına ilişkin cinsiyet farklılıkları ve cinsiyet kimliği farklılıklarının zaten var olduğunu ve androjen bireylerin satış mesleği için en uygun cinsiyet kimliğine sahip olduğunu belirlemiştir (Tanrıkulu, 2017, s. 499). Acar ( 2012), cinsiyetle kurumsal marka değerinin algılanmasını incelediği araştırmasında, iki cins arasında bir ayrımın söz konusu olmadığını ancak tüketicilerin kurumsal markayı önemsedikleri sektörle cinsiyet arasında ilişki bulunduğunu belirlemiştir (Acar, 2012, s. 118).…”
Section: Literatür Taramasıunclassified
“…İlgili yazında, örgütsel stresin cinsiyet bazında nasıl algılandığını ve nasıl reaksiyon gösterildiğini ortaya koyan çeşitli araştırmalara (Lim ve Teo, 1996;Vagg vd., 2002;Wu ve Shih, 2010;Torres vd., 2013;Tandon vd., 2014;Tanrıkulu, 2017) rastlamak mümkündür. Bazı araştırmalarda örgütsel stres kaynaklarına dönük algının ve oluşan reaksiyonların, cinsiyet temelinde farklılaştığı öne sürülürken, birtakım araştırmalarda söz konusu algı ve reaksiyon farklılıklarının var olmadığı dile getirilmektedir.…”
Section: öRgütsel Stres-cinsiyet İlişkisiunclassified